(untitled) (Community Based Medical Journal, 2025)
Bronchiectasis is a heterogeneous condition characterized by chronic airway inflammation. Phenotypic classification into neutrophilic, eosinophilic, and non-neutrophilic types is crucial for understanding disease pathophysiology and guiding management. A cross-sectional study was conducted in the Department of Respiratory Medicine, Cumilla Medical College Hospital, Bangladesh, from January 2023 to June 2024, to assess prevalence of those phenotypes and clinical implications. A total of 150 adult bronchiectasis patients diagnosed via clinical features, high-resolution computed tomography (HRCT), and pulmonary function tests. Blood samples were analyzed to determine phenotypes: neutrophilic (ANC >7.5×10⁹/L), eosinophilic (AEC >0.3×10⁹/L), and non-neutrophilic (neither criteria met). Clinical, demographic, and radiological data were collected and analyzed. The neutrophilic phenotype was predominant (63.3%), followed by eosinophilic (23.3%) and non-neutrophilic (13.4%). Neutrophilic patients were older (mean 45.3±10.5years) and more likely to be smokers (57.9%; p=0.015). Frequent exacerbations (>2 per year) were highest in neutrophilic (68.4%; p=0.001), and severe HRCT findings were more prevalent in this group (57.9%; p=0.048). Eosinophilic patients had milder disease and fewer exacerbations (57.1%), aligning with a Th2-driven inflammatory mechanism. Logistic regression showed smoking as a significant risk factor for severe disease (OR=2.08, p=0.019). Neutrophilic bronchiectasis is the most common and severe phenotype, closely linked to smoking and frequent exacerbations. Eosinophilic and non-neutrophilic phenotypes showed milder clinical courses highlighting the need for management strategies tailored to specific phenotypes. CBMJ 2025 July: vol. 14 no. 02 P:21-27